Analysis of environmental factors with the incidence of stunting in toddlers (literature review) - Yurizal Yurizal; Najmah Najmah; Anita Rahmiwati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Abstract Background: The potential for a pandemic to trigger an increase in the malnutrition crisis in 2020 is that 132 million people suffer from hunger and 370 million school-age children do not receive adequate food, as well as 6.7 million The potential for triggering a pandemic triggering a malnutrition crisis in 2020 is that 132 million people suffer and 370 million school-age children do not get enough food, and 6.7 million neglected children in addition to 2019 before the pandemic 47 million children are deprived and 14 million children stunting. The problem of malnutrition is caused by environmental factors (insufficient sanitation and drinking water sources), inadequate health services, low knowledge of maternal nutrition, and poor feeding practices. The purpose of the study was to analyze environmental factors with the incidence of stunting in children under five based on the results of internationally published health research. Method: The research design is a literature review, by conducting a literature search through international journal articles from 2018-2022 regarding stunting in toddlers. Correlation research articles used cross sectional, case control and cohort studies. The research population is all research articles in published journals regarding the analysis of environmental factors with the incidence of stunting in toddlers through the ScienceDirect, Biomed Central, PubMed, SAGE journals, ProQuest and Google Scholar databases, while the sample is the relevant articles. Results: The incidence of stunting is still high in Indonesia with a prevalence rate of 19%-61.8%, mostly caused by environmental factors including sources of drinking water, sanitation facilities and latrines as well as hygiene practices. Conclusion: Environmental factors are factors related to the incidence of stunting in toddlers. Key words: Stunting, Environmental Factors, literature review